Montagem e análise taxonômica-funcional de transcriptomas de espécies de cupins brasileiros - Martins, Leonardo do Amaral (2020)
Termites (Isoptera) are eusocial insects that stand out for their hierarchical and structural organization, demonstrating complex social behaviors, numerous symbiotic interactions, and a great potential for bioprospecting enzymes of industrial interest. In addition, they are also frequent pests of Brazilian agricultural monocultures. Despite the importance of this species, molecular studies on termites have not yet been sufficient so that the mechanisms that control phenotypic plasticity in these insects have been completely elucidated. In this exploratory study, we performed a comparative inter and intraspecific analysis between termite transcriptomes of the Brazilian species Heterotermes tenuis, Cornitermes cumulans and Velocitermes heteropterus, as well as a biodiversity survey of their endosymbiotic microbiota and prospecting of genes with biotechnological potential. Important differences were found between the lower and the higher species when compared in terms of their taxonomic diversity, including the surprising detection of flagellate symbionts in the higher species, with emphasis on the great presence of the phylum Amoebozoa. Our analysis of differential expression showed that the majority of the annotated genes were unique to a certain caste or species, and their functional annotation showed differences in biological processes, especially among the castes of higher species. Among the most differentially expressed genes of each species, we found genes with potential for use in the management of termites as pests and for industrial applications, e.g., hexamerins, cytochrome P450 and many cellulases. Together, these results enhance the knowledge about the plasticity observed through the castes and open new perspectives for future biotechnological applications.